E-SMART 2.0: a sustainable bin for e-waste disposal - Raja Zulkifli@Wan Zulkifli, Raja Nur Izny Kamaliyah; Tengku Sahrum, Tengku Nurshazwina; Ahmad, Abdur Rahman Sudais; Ahmad Taufiq, Muhammad Mukhlis; Mohd Yusof, Mohd Idham (Universiti Teknologi MARA, Kedah, 2023)
Under Sustainable Development Goal (SDG) 11 on Sustainable Cities and Communities, e-waste is recognised as a global problem. E-waste production has been studied by numerous scholars and statistics show an increasing trend. It was reported that Malaysians as a whole produce over 365,000 tonnes of e-waste each and every year. The manner in which this e-waste was managed and disposed of has been one of the major concerns to the government, authorities managing the environment and the public at large. Based on the issue, we innovate a product known as E-SMART 2.0. This is a portable and sustainable smart bin that will make it easier for the public to dispose of and sort their small e-waste (i.e. unused handphones, batteries and small electronic devices) in an environmentally responsible manner. This innovative product may be utilised by numerous stakeholders such as government agencies (i.e., schools, universities, and local government buildings), the private sector, or other waste management authorities to educate the general public to be aware of how to dispose of their e-waste in a sustainable manner. Based on the Social Exchange Theory, the idea of E-SMART 2.0 is to reward each item of e-waste with cash, and the purpose of this incentive is to encourage sustainable behaviour. This bin is portable and can be placed in public areas as well as at public events. It is sustainable, safe, informative and friendly to the environment. Subsequently, it has the potential to promote SDG11 which focuses on sustainable cities and communities and other relevant SDG goals. The implementation of ESMART 2.0 required partnership from various stakeholders, illustrating commitments towards environmental sustainability. In future, the effectiveness of E-SMART 2.0 needs to be explored on how it transformed the general public to become a sustainable society with sustainable behaviour.